Obtenção e caracterização de microesferas de copolímero PLDLA contendo paclitaxel - Martins, Kelly Fernanda (Universidade Federal de São Carlos, 2013)
In order to minimize the side effects of chemotherapy concurrently with the enhancement of its therapeutic action is to use it on devices that enable a controlled drug release, by vectors, such as polymeric microspheres, which act as a drug carrier, modifying its distribution pattern in the organism. Paclitaxel ((Taxol®) is a drug used primarily in the treatment of ovarian, breast, lung and bladder cancer. Due to its antimitotic and antiproliferative action, there is a potential interest in cancer therapy. However, the success of this clinical application is limited to low solubility in water and toxic action. The objective of this study was to obtain and characterize physic-chemically the bioresorbable and biocompatible copolymer poly (L-co-D, L lactic acid) (PLDLA) microspheres encapsulating the paclitaxel chemotherapy. The simple emulsion technique allowed to obtain spherical microspheres, verified by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The average size of the microspheres PLDA pure and containing paclitaxel were, respectively, 10.3 μm ± 1.7 and 12.7 μm ± 1.3, obtained by the technique of laser light scattering (LLS). Moreover the essay of differential scanning calorimetry (DSC) suggests that the drug paclitaxel is homogeneously dispersed in the microspheres PLDLA. The encapsulation efficiency of the microspheres PLDLA paclitaxel was 98.0% ± 0.3, obtained by high performance liquid chromatography (HPLC). The in vitro release study performed on HPLC showed initial burst release followed by a slower release, which characterizes large diameter distribution systems. PLDLA microspheres released 90% ± 4.0 of the drug paclitaxel up to 30th day of study while the degradation process occurred. Thus, the microspheres obtained PLDLA devices are promising as carriers of paclitaxel, with potential for future applications in drug delivery systems.
Obtaining and characterization of the copolymer PLDLA microspheres containing paclitaxel
Keywords: Biomateriais; polímeros (materiais); microesferas - uso terapêutico; PLDLA; microesferas; paclitaxel; quimioterápico; microspheres; PLDLA; paclitaxel; chemotherapeutic; CIENCIAS EXATAS E DA TERRA